Effects of continuous and rotation tillage practices on stratification of selected soil chemical parameters and canola productivity in the Swartland, South Africa - Mabitsela, Mmakwena Velicia (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2025.